2017
DOI: 10.1097/md.0000000000005943
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance (MR) imaging for tumor staging and definition of tumor volumes on radiation treatment planning in nonsmall cell lung cancer

Abstract: We investigate the impact of magnetic resonance (MR) on the staging and radiotherapy planning for patients with nonsmall cell lung cancer (NSCLC).A total of 24 patients with NSCLC underwent MRI, which was fused with radiotherapy planning CT using rigid registration. Gross tumor volume (GTV) was delineated not only according to CT image alone (GTVCT), but also based on both CT and MR image (GTVCT/MR). For each patient, 2 conformal treatment plans were made according to GTVCT and GTVCT/MR, respectively. Dose-vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…DW-MRI has become an indispensable tool in cancer research, diagnosis and treatment, and it has been suggested that DWI combined with MRI can provide important information in differentiating lung cancer and atelectasis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DW-MRI has become an indispensable tool in cancer research, diagnosis and treatment, and it has been suggested that DWI combined with MRI can provide important information in differentiating lung cancer and atelectasis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deniaud-Alexandre et al (40) revealed that PET/CT can provide different GTVs from the traditional CT plan in patients with non-small cell lung cancer and can also change the estimated receiving dosage of heart and lungs. DW-MRI has become an indispensable tool in cancer research, diagnosis and treatment, and it has been suggested that DWI combined with MRI can provide important information in differentiating lung cancer and atelectasis (41).…”
Section: P-values Amentioning
confidence: 99%
“…At present, most drug delivery systems can only deliver drugs to cancer cells, and the distribution and release of drug delivery systems in cancer cells cannot be monitored. In order to further develop and optimize drug delivery systems, a multifunctional nanomedicine platform for imaging diagnosis and therapy is needed ( Zhao et al, 2017 ; Wang et al, 2020 ). The usual approach is to integrate fluorescent dyes into the drug delivery system.…”
Section: Introductionmentioning
confidence: 99%